Application range of the HEM approach for CO2 expansion inside two-phase ejectors for supermarket refrigeration systems. (November 2015) - Palacz, Michal; Smolka, Jacek; Fic, Adam; Bulinski, Zbigniew; Nowak, Andrzej J.; Banasiak, Krzysztof; Hafner, Armin
Highlights: The accuracy of the HEM approach for the R744 expansion inside ejectors was assessed. The HEM accuracy decreases with the decreasing motive nozzle inlet temperature. The HEM guarantee accurate results for operating regimes close to the CO2 critical point. Abstract: In this study, the accuracy of the homogeneous equilibrium (HEM) applied to 3-D CFD-based simulations of CO2 expansion inside two-phase ejectors is presented. The HEM approach previously reported in the literature was assessed by comparing the computed and measured mass flow rates that pass through an ejector motive nozzle. In addition, the HEM approach implemented using CFD was tested over a vast range of ejector operating regimes. To ensure that all of the computations were performed consistently, a validated CFD model combined within an in-house developed script was used. The comparison of the experimental and computational results showed that the HEM accuracy varied for the different sets of operating parameters. Accurate results were obtained for operating regimes near or above the CO2 critical point. The model accuracy decreased with the decreasing temperature and decreasing distance to the saturation line.